2014
DOI: 10.1177/1470320314539181
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin converting enzyme intron 16 insertion/deletion genotype is associated with plasma C-reactive protein concentration in uteroplacental dysfunction

Abstract: Introduction: Disturbance of the uteroplacental circulation (UPC) and the renin-angiotensin system are involved in the pathogenesis of preeclampsia. In women with history of preeclampsia persistently elevated C-reactive protein (CRP) levels have been described. The angiotensin-converting enzyme (ACE) intron 16 insertion/deletion (I/D) genotype is associated with ACE activity and assumed to be a risk factor for preeclampsia. As ACE generates proinflammatory angiotensin II, we analysed, whether ACE intron 16 I/D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…Dysfunction of the RAAS, in particular changes to angiotensin II, during pregnancy is implicated in preeclampsia. 67 Inflammation (as measured by CRP levels) in pregnant women exhibiting altered utero–placental function was associated with an insertion/deletion polymorphism in the angiotensin-converting-enzyme gene responsible for the conversion of angiotensin II from angiotensin I. 67 Lasting changes to endothelial function are also observed in postpartum women with a past history of preeclampsia who display enhanced vasoconstriction sensitivity to angiotensin II, 68 suggesting that increased sensitivity to angiotensin II may contribute to persisting vasculature dysfunction and increase risk for future CVD.…”
Section: Raasmentioning
confidence: 99%
“…Dysfunction of the RAAS, in particular changes to angiotensin II, during pregnancy is implicated in preeclampsia. 67 Inflammation (as measured by CRP levels) in pregnant women exhibiting altered utero–placental function was associated with an insertion/deletion polymorphism in the angiotensin-converting-enzyme gene responsible for the conversion of angiotensin II from angiotensin I. 67 Lasting changes to endothelial function are also observed in postpartum women with a past history of preeclampsia who display enhanced vasoconstriction sensitivity to angiotensin II, 68 suggesting that increased sensitivity to angiotensin II may contribute to persisting vasculature dysfunction and increase risk for future CVD.…”
Section: Raasmentioning
confidence: 99%
“…Считается, что D аллель ассо-циируется с повышенной концентрацией ангиотензинпре-вращающего фермента [7,22] и С-реактивного белка [26] в сыворотке крови, сниженной активностью ренина плазмы [6] и компонентов системы антиоксидантной защиты [40], нарушениями процессов вазодилатации [6], а также гисто-патологическими изменениями сосудов матки [11] -то есть с факторами, которые могут быть задействованы в патоге-незе преэклампсии. Все это и обусловливает повышенную склонность к развитию гипертензивных осложнений во время беременности у носителей D аллеля гена АСЕ.…”
Section: илиunclassified
“…Valdez et al (2007) found that the D allele of ACE gene I/D polymorphism was significantly associated with premature rupture of membranes in the Mexican population [17]. Häupl et al (2015) showed a significant association between ACE gene I/D polymorphism and uteroplacental dysfunction in the Middle Eastern Asian population [18]. Uma et al (2008) observed that the DD genotype of ACE gene I/D polymorphism was associated with the development of PTB in the Caucasian population [19].…”
Section: Introductionmentioning
confidence: 99%